2016
DOI: 10.1111/jar.12304
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Trends and Custody Among Children of Parents with Intellectual Disabilities in Norway

Abstract: The results show that prevalence depends on the definition of intellectual disability. The decreasing number of children and the need for development of specially adapted family supports are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 14 publications
3
29
0
1
Order By: Relevance
“…12 -14, 19 Most studies were restricted to high-risk samples from court documents 12,13,19 or social service agency records. 14 In addition, although 1 study suggested that younger child age was associated with increased odds of court applications for guardianship orders, 19 only 2 studies specifically examined custody loss directly after delivery. 15,16 The only other population-based study revealed that, among 53 565 women in Manitoba, Canada, of whom 69 had an IDD, IDD status was associated with 6.54 greater odds of having an infant taken into care at birth, 16 consistent with our aRR of 8.10.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 -14, 19 Most studies were restricted to high-risk samples from court documents 12,13,19 or social service agency records. 14 In addition, although 1 study suggested that younger child age was associated with increased odds of court applications for guardianship orders, 19 only 2 studies specifically examined custody loss directly after delivery. 15,16 The only other population-based study revealed that, among 53 565 women in Manitoba, Canada, of whom 69 had an IDD, IDD status was associated with 6.54 greater odds of having an infant taken into care at birth, 16 consistent with our aRR of 8.10.…”
Section: Discussionmentioning
confidence: 99%
“…15, 17 -20 However, only 2 studies have been focused on the newborn period, 15,16 with authors of most studies failing to consider age at removal. 12 -14, 17, 18 Other than 1 population-based study, 16 data are primarily from court documents 12, 13, 18 -20 and social service agency records, 14,15,17 which are used to capture high-risk groups. Also, many studies do not have comparison groups without IDDs or with IDDs but no custody loss, making it difficult to explain disparities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the research in this area comes from Anglo‐Saxon countries and applies to persons with IDs. According to some research, almost 25% of all child care proceedings may involve parents with IDs (Azar, Maggi, & Proctor, ; Booth & Booth, ; Tøssebro, Midjo, Paulsen, & Berg, ). For this category of parents, there are indications of discrimination in child care proceedings and in courts (Booth, Mcconnell, & Booth, ), in Sweden as elsewhere (Alexius & Hollander, ).…”
Section: Introductionmentioning
confidence: 99%
“…Six decades later, researchers continue to document high rates of child custody deprivation. In this issue, LaLiberte, Piescher, Mickelson, and Lee (USA), and Tøssebro, Midjo, Paulsen, and Berg (Norway) document disproportionate representation and differentially intrusive outcomes for children of parents with intellectual disabilities caught up in the child welfare system. Analysing large administrative data sets in Norway, Tøssebro et al. find that parental intellectual disability is noted in 20‐25% of all cases in which child welfare services assume custody.…”
Section: Research Impactmentioning
confidence: 99%